GENETIC ANALYSIS OF FORAGE QUALITY TRAITS IN SORGHUM-SUDANGRASS HYBRIDS UNDER WATER STRESS - A. Bibi; H. A. Sadaqat; M. H. N. Tahir; B. Fatima Usman; M. Ali (Journal of Animal and Plant Sciences, 2012)
Forage as a feed for livestock in emergency period has always been a dire need of the time. Field experiments were conducted during 2007 and 2008 to estimate the specific and general combining ability effects for forage quality traits in sorghum-sudangrass hybrids by using ten lines of sorghum and five testers of sudangrass using line and tester mating fashion under normal as well as water stress conditions. Generally reduction has been observed in all forage quality components except crude protein and nitrogen free extracts under water stress conditions. The average values were recorded as 31.66% for sugar contents; 11.01% for leaf to stem ratio; 19.23% for crude fibre; 22.69% and 3.37% for ether extract and total ash respectively. While the increase percentage best general combiner genotype was 8614 for leaf to stem ratio, crude protein, nitrogen free extracts and ether extracts under normal as well as water stress conditions. While the best female parent was the genotype 80364 for sugar contents, leaf to stem ratio and crude protein contents. It was concluded that 8614 and 80364 genotypes may be used for the development of good quality sorghum-sudangrass forage hybrids.
Keywords: Forage; quality; sorghum; sudangrass; water stress; GCA; SCA.